5-HT1B receptor agonist enhances breakpoint for cocaine on a progressive ratio (PR) schedule during maintenance of self-administration in female rats but reduces breakpoint for sucrose - Scott, Samantha N.; Ruscitti, Brielle A.; Garcia, Raul; Nguyen, Toan T.; Blattner, Kevin M.; Blass, Benjamin E.; Neisewander, Janet L. (Frontiers in Behavioral Neuroscience, 2022)
Abstract Background: Previous research showed that the 5-HT1B receptor agonist CP94253 enhanced cocaine reinforcement rate during maintenance of daily self-administration (SA), but inhibited reinforcement rate after 21 days of abstinence in male rats. Here we examined whether female rats show similar effects of CP94253 during maintenance as males across estrous cycle phases. Methods: Female rats trained on a fixed ratio 5 (FR5) cocaine reinforcement schedule were tested for the effects of CP94253 (5.6 mg/kg, s.c.) on cocaine reinforcement rate during each phase of the estrous cycle, with access to either low (0.075 and 0.1875) or high (0.375 and 0.75) cocaine doses available for 1 h sequentially in descending dose order. Other female and male rats trained on a progressive ratio (PR) schedule of cocaine or sucrose reinforcement were tested for CP94253 (0, 3.2, 5.6, and 10 mg/kg, s.c.) effects on reinforcement rate in 3-h sessions. CP94253 effects on responding during sucrose cue-reactivity were also examined post-abstinence. Results: Regardless of sex, CP94253 enhanced breakpoints on the PR schedule during maintenance of cocaine SA but attenuated breakpoints for sucrose reinforcement and decreased responding during sucrose cue-reactivity. FR results showed that CP94253 attenuated cocaine reinforcement rate during all estrous cycle phases except metestrus. Conclusions: Overall, we suggest that CP94253 increased incentive motivation for cocaine during maintenance of SA in female and male rats, yet decreased motivation for sucrose. We also suggest that 5-HT1BRs modulate motivation similarly across sexes except when females are in metestrus.